f(x) = x²-5x+6 one zero of the polynomial is 2 then g(x) = (x-2) By dividing f(x) from g(x) we get the other zero of the polynomial x-2) x²-5x+6( x-3 x²-2x ___(-)_(+)__________ -3x +6 -3x +6 _____(+)__(-)_______ 0 _________________ Therefore the other zero of the polynomial is x-3 = 0 x = 3 Hope it helps you Please mark my answer as brainliests Reply

one zero of the polynomial is 2 we know that sum of zeros will be -b/a here b=-5 a=1 -b/a=2+x -(-5)/1 = 2+x 5 = 2+x 5-2 = x 3 = x Reply

f(x) = x²-5x+6

one zero of the polynomial is 2 then

g(x) = (x-2)

By dividing f(x) from g(x) we get the other zero of the polynomial

x-2) x²-5x+6( x-3

x²-2x

___(-)_(+)__________

-3x +6

-3x +6

_____(+)__(-)_______

0

_________________

Thereforetheotherzeroofthepolynomialisx-3=0x=3HopeithelpsyouPleasemarkmyanswerasbrainliestsone zero of the polynomial is 2

we know that sum of zeros will be -b/a

here b=-5

a=1

-b/a=2+x

-(-5)/1 = 2+x

5 = 2+x

5-2 = x

3 = x